John Rawls: una biografía* (2010)
Translation of the original in English: Leonardo García Jaramillo and María Graciela Otoya Diehn. First published in Spanish thanks to the permission of Thomas Pogge. This essay originally appeared in German and was part of the book John Rawls (Munich: Ve